Pengaruh Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Organizational Citizenship Behavior (OCB) Sebagai Variabel Intervening - Teguh Wicaksono; Muhammad Gazali (Islamic University of Kalimantan MAB Banjarmasin, 2021)
This study aims to examine and analyze the effect of job satisfaction on organizational citizenship behavior, both on the direct and indirect effect on employees of favehotel Ahmad Yani Banjarmasin. This study uses an explanatory research method with a quantitative approach. The data analysis method used is descriptive analysis and path analysis. The study population was all employees of favehotel ahmad yani Banjarmasin and a sample of 67 respondents. The results of this study indicate that Job Satisfaction has a significant effect on Organizational Citizenship Behavior with a path coefficient value of 0.604. Organizational Citizenship Behavior has a significant effect on employee performance with a path coefficient value of 0.320. Job Satisfaction has a significant effect on Employee Performance with a path coefficient value of 0.280. Organizational Citizenship Behavior does not mediate job satisfaction on employee performance with a direct effect value that is greater than the indirect effect.